Potential Object Mapping of Nagari Batuhampar Religious Tourism Destination for Sustainable Development in Limapuluh Kota District - Susetyo, Bigharta Bekti; Novio, Rery; Prarikeslan, Widya; Sutriani, Widia; Ferdian, Feri (Digital Press Social Sciences and Humanities, 2020)
Nagari Batuhampar is a village located in Akabiluru District, Limapuluh Kota Regency. Nagari Batuhampar has physical and social potential that can be used as a tourist destination. This has been planned in the Nagari Strategic Plan which will develop tourism in the form of religious tourism. However, the problem in the field is that there is no map as a reference for regional development. The Nagari government views the importance of making this map as an aspect of regional development decision making. This research is classified as a descriptive quantitative survey research, which explains the phenomena in the field in accordance with the original situation. The purpose of this study is to map the location of the objects of religious tourism destinations in Nagari Batuhampar. This is intended so that the development of tourism-based areas is more monitored, mapped, planned, and evaluated. The result of the research states that the tourism object location points are along the road. This can be developed later to diversify attractions between tourism locations.